2010
DOI: 10.1056/nejmsa0907115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bar-Code Technology on the Safety of Medication Administration

Abstract: Use of the bar-code eMAR substantially reduced the rate of errors in order transcription and in medication administration as well as potential adverse drug events, although it did not eliminate such errors. Our data show that the bar-code eMAR is an important intervention to improve medication safety. (ClinicalTrials.gov number, NCT00243373.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
258
1
15

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 469 publications
(279 citation statements)
references
References 25 publications
5
258
1
15
Order By: Relevance
“…A recently published work by Poon et al [10] clearly demonstrated the advantages of using bar code technology in terms of the safety of medication administration. Providing computerized charts that sound an alarm when drugs that should be avoided in a patient with known DH are prescribed should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published work by Poon et al [10] clearly demonstrated the advantages of using bar code technology in terms of the safety of medication administration. Providing computerized charts that sound an alarm when drugs that should be avoided in a patient with known DH are prescribed should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Screen accesses were calculated at each site and a median of 20 screens were accessed per patient visit at UAH (IQR: 6-67), 9 at GNCH (4-29), 7 at FMC (2-18) and 5 at PLC (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). When compared with the structured clinical observations, the statistical analysis of screen access data also showed that ANP was used more at UAH than the other sites.…”
Section: Physician Interviewsmentioning
confidence: 99%
“…The adoption and use of an Electronic Health Record (EHR) can facilitate real-time access to key health information and support improved outcomes [1][2][3][4][5][6][7][8][9]. Canada's hospitals are still primarily paper-based, with only 5.2% of hospitals progressing to stage five or higher on the on the seven point Electronic Medical Record Adoption Scale [10].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice settings where eMAR systems are used effectively, statistically significant reductions in medication errors in comparison to those using paperbased medication administration processes have been reported [14]. Due to ongoing high rates of adverse medication events in both Canada and the United States [15,16], clinical technology like eMARs may be essential for the reduction of medication-related errors [17,18].…”
Section: Electronic Medication Administration and Nursing Educationmentioning
confidence: 99%